The Social Contract Or Traditional Elements In The Federal Constitution Of Malaysia: An Analysis Of Its Application - Khadijah Muda; Nazri Muslim; Fazilah Idris; Siti Nor Azhani Mohd Tohar (Human Resource Management Academic Research Society, 2024)
Indexed by ERA